1989
DOI: 10.1002/pen.760291408
|View full text |Cite
|
Sign up to set email alerts
|

A sub‐0.5 μm bilevel lithographic process using the deep‐UV electron‐beam resist p(si‐cms)

Abstract: Optimization of the deep‐UV and electron‐beam lithographic properties of a copolymer of trimethylsilylmethyl methacrylate (SI) and chloromethylstyrene (CMS), P(SI‐CMS), within a weight average molecular weight range of 1.4 to 4.1 × 105 and 90 to 93 mole percent SI composition has been achieved. The solubility behavior of P(SI‐CMS) resist was examined using the Hansen 3‐dimensional solubility parameter model and dissolution rate measurements. Swelling of the resist has been minimized through the identification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Other resists that exhibit acceptable thermal prop erties and etching resistance for bilevel applications are copolymers of trimethylsilyl- (36,37) and trimethylstanylstyrene (36) with chlorostyrene. Additionally, copolymerization of trimethylsilylmethyl methacrylate with chloromethylstyrene yields a viable electron-beam and deep-UV negative resist even though the homopolymer of the silicon-containing methacrylate is a posItive acting material (38). In this case, at the exposure doses employed, crosslinking of the chloromethylstyrene units in this resist pre dominates, and the silyl metharylate serves only to provide the source of silicon in the resist.…”
Section: Single Component Crosslinking Resistsmentioning
confidence: 97%
“…Other resists that exhibit acceptable thermal prop erties and etching resistance for bilevel applications are copolymers of trimethylsilyl- (36,37) and trimethylstanylstyrene (36) with chlorostyrene. Additionally, copolymerization of trimethylsilylmethyl methacrylate with chloromethylstyrene yields a viable electron-beam and deep-UV negative resist even though the homopolymer of the silicon-containing methacrylate is a posItive acting material (38). In this case, at the exposure doses employed, crosslinking of the chloromethylstyrene units in this resist pre dominates, and the silyl metharylate serves only to provide the source of silicon in the resist.…”
Section: Single Component Crosslinking Resistsmentioning
confidence: 97%
“…5 It is a copolymer of trimethysilylmethyl methacrylate ͑SI͒ and chloromethylstyrene ͑CMS͒. Recently, studies have shown P͑SI-CMS͒ to be a high resolution, high contrast, and high sensitivity resist.…”
Section: Introductionmentioning
confidence: 99%